2014
DOI: 10.1159/000362389
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Brain Metastases

Abstract: Brain metastases are associated with substantial morbidity and mortality. Key prognostic classification systems for brain metastases are reviewed. The role of surgery, particularly for single brain metastases, is discussed. This is followed by an overview of radiation, both whole brain and focal, in the treatment of brain metastases. Finally, we review examples of important concepts regarding the role of systemic therapy in the treatment of brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…Most studies (reviewed in [26, 62, 72, 78, 80, 81]) have clearly demonstrated that the addition of WBRT to surgery or SRS was associated with improved local control rates and decreased neurologic deaths but did not improve outcome in terms of survival (class I evidence). With respect to BMHCC, a retrospective study by Choi et al [33] concluded that resection in conjunction with WBRT showed considerably prolonged survival (33.6 weeks).…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (reviewed in [26, 62, 72, 78, 80, 81]) have clearly demonstrated that the addition of WBRT to surgery or SRS was associated with improved local control rates and decreased neurologic deaths but did not improve outcome in terms of survival (class I evidence). With respect to BMHCC, a retrospective study by Choi et al [33] concluded that resection in conjunction with WBRT showed considerably prolonged survival (33.6 weeks).…”
Section: Radiotherapymentioning
confidence: 99%
“…SRS has become an increasingly popular treatment option for patients with 1-4 metastases [81], and can be considered as an alternative for surgery or a salvage treatment in patients who are not candidates for surgery [74, 8284]. Typically, when the metastases are larger than 3-4 cm or immediate mass relief is required, surgery is preferred [63, 74].…”
Section: Radiotherapymentioning
confidence: 99%
“…Important advances in our understanding of brain metastases are underway [ 1 , 2 ]. While there have been many recent reviews of brain metastases [ 3 6 ] as well as more focused reviews on non-small cell lung cancer (NSCLC) brain metastases [ 7 9 ] there has been a paucity of contemporary reviews focusing on small cell lung cancer (SCLC) brain metastases. A broad overview of SCLC can be found in a recent review [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this update, we first discuss ongoing and future developments in the neurosurgical management of both metastatic and primary CNS tumors, before shifting to the medical management of high-grade gliomas (HGG). The overall management of CNS metastases 1 and gliomas 2 has been reviewed recently, and so here we focus on how neurosurgical interventions will feature within the wider context of the ongoing advances in neuro-oncology. 3…”
Section: Goals Of Neurosurgical Interventionmentioning
confidence: 99%